Hubungan Pengetahuan dan Sikap Ibu Menyusui Dengan Pemberian Kolostrum di Desa Tanjung Wilayah Kerja Puskesmas Limbur Tembesi - Sari Batubara, Hamidah; Rosita Hutagaol, Uli; Andriani, Andriani; Septalia Dale, Dewinny; Sri Wahyuni, Rika (UNIVERSITAS HAJI SUMATERA UTARA, 2025)
Colostrum is the first stage of breast milk production. This slightly yellowish colostrum contains 10-17 times more antibodies than mature breast milk to protect babies from substances that can cause allergies or infections before receiving complete basic immunization. In Sarolangun City, the percentage of newborns who received early breastfeeding initiation from 5,174 newborns was 4,627 (73.61%) and from 5,633 babies aged <6 months who received exclusive breastfeeding, 2,978 (52.87%) (Jambi Province Health Profile, 2019). The purpose of this study was to determine the Relationship between Knowledge and Attitudes of Breastfeeding Mothers with the Provision of Colostrum in Tanjung Village, Limbur Tembesi Health Center Work Area in 2023. This research method is a type of research using quantitative with a quantitative descriptive design. The population in this study was 52 respondents. Samples were taken using the total sampling technique. Data were collected using a questionnaire. Data analysis was done univariately and bivariately using the Chi-Square test. This study found a significant relationship between maternal knowledge and colostrum administration.